Nonnus' Paraphrase between Poetry, Rhetoric and Theology : Rewriting the Fourth Gospel in the Fifth Century - Ypsilanti, Maria, (Mnemosyne, Supplements ;, 2021)
This book investigates the various paraphrastic techniques employed by Nonnus of Panopolis (5th century CE) for his poetic version of the Gospel of John. The authors look at Nonnus' Paraphrase , the only extant poetic Greek paraphrase of the New Testament, in the light of ancient rhetorical theory while also exploring its multi-faceted relationship with poetic tradition and the theological debates of its era. The study shows how interpretation, cardinal both in ancient literary criticism and in theology, is exploited in a poem that is exegetical both from a philological and a Christian point of view and adheres, at the same time, to the literary principles of Hellenistic times and late antiquity.